2022
DOI: 10.1101/2022.02.02.22270345
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trend and Weightage of Problem-based Questions in Undergraduate Pharmacology Written Question Papers of Bangladesh

Abstract: Background: The key objective of pharmacology education is to make graduates competent enough to prescribe safely and effectively. There is worldwide speculation of inadequacy of pharmacology education to achieve the expected learning outcomes. Problem-based pharmacotherapy is considered as one of the crucial way to prepare future physicians as rational prescribers. As assessment drives learning priorities, adequate weightage on problem-based questions in undergraduate pharmacology examination might be helpful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…14,15 Interuniversity variation in weightage of dermatological pharmacotherapy was also found, and this finding is concordance with published literatures which showed interuniversity variation of pharmacology question papers in regards to curricular objectives, content coverage, nation health priorities and problembased problem. 20,21 Skin diseases comprise a certain percentage of patient bulk in outdoor department of primary care in Bangladesh and treated by MBBS doctor. 24 So appropriate weightage on dermatological pharmacotherapy might improve quality of healthcare as well as quality of life of a large group of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Interuniversity variation in weightage of dermatological pharmacotherapy was also found, and this finding is concordance with published literatures which showed interuniversity variation of pharmacology question papers in regards to curricular objectives, content coverage, nation health priorities and problembased problem. 20,21 Skin diseases comprise a certain percentage of patient bulk in outdoor department of primary care in Bangladesh and treated by MBBS doctor. 24 So appropriate weightage on dermatological pharmacotherapy might improve quality of healthcare as well as quality of life of a large group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…13 Several studies were conducted in Bangladesh to evaluate pharmacology education (curriculum, textbooks and question papers) from different perspectives. [14][15][16][17][18][19][20][21] In this backdrop, current study was conducted to evaluate pharmacology curriculum and written question papers of last 10 years with the attempt to find out the weightage and trend of dermatological pharmacotherapy in undergraduate pharmacology curricula and written assessment system.…”
Section: Original Articlementioning
confidence: 99%
“…23,24 One recent study conducted in Bangladesh revealed pharmacology written question papers of different universities under guidance of same curriculum of BMDC differ in the aspect of weightage of problem-based questions. 36…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancy between allocated teaching times and weightage given in written exam, missing the spirit of the curriculum, lack of questions on evaluating problem solving skill, less focus on issues related to antimicrobial resistance and absence of factors influencing prescribing e.g. ethics, moral values, pharmaceutical promotion and critical appraisal were revealed in previous studies 7,[20][21][22][23][24] . In this backdrop, current study was an attempt to illustrate the reflection of curricular objectives, content coverage and national health priorities in the Pharmacology written question papers of last 10 years.…”
Section: Introductionmentioning
confidence: 99%